ISTILAH KEKERABATAN DALAM BAHASA SASAK - Nurlaela Zuhma Yani (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
The term kinship in Sasak society is interesting to research, especially the division based on consanguinal and afinal terms. Therefore, this study aims to elaborate the consanguinal and final terms of the Sasak community in Gontoran Village. In this study, data collection used free interview methods, data analysis using extralingual methods, and presentation of data analysis results using informal methods.